Strategi Manajemen Konflik Dalam Meningkatkan Kinerja Dosen di Universitas Teknologi Sulawesi Utara - Diana Wangania; Michiko Nishino; Hendry Rumengan; Stephanus Stephanus; Roland Londok; Rosmini Wali; Yonatan Tumangkeng (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Conflict can happen in all organizations including universities. Lecturers in universities are one of the important actors in the organization and may be involved in conflicts with each other or with other parties in the university. Therefore, conflict management becomes important to improve lecturer performance in universities. This study uses qualitative research methods with the aim of exploring conflict management strategies used to improve lecturer performance at the North Sulawesi University of Technology. The results of the study indicate that effective conflict management strategies to improve lecturer performance include a collaborative approach, improved communication, recognition of the role and contribution of lecturer, appreciation of cooperation, and conflict resolution through mediation. Therefore, there needs to be careful attention and planning in conflict management to improve lecturer performance in university.